Improving the Efficiency of Patient Discharge Time and Health Insurance Claim Administration through Lean Implementation - Siswoyo, Siswoyo; Hernawati, Sri; Firman, Firman (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Health services in the era of the National Health Insurance system require hospitals to achieve not only optimal clinical outcomes but also operational efficiency. RSD dr. Soebandi, located in Jember, Indonesia, experienced performance problems in its inpatient unit, particularly in two areas: the average patient discharge waiting time exceeded the hospital standard of less than two hours, and the inpatient insurance claim administration process to BPJS Kesehatan exceeded the required 2×24-hour completion target. These issues were identified as forms of waste, especially waiting time. This study aimed to analyze the efficiency of the inpatient discharge process and insurance claim administration, and to identify and implement Lean-based solutions to reduce operational waste. This study employed Action Research with a mixed-methods approach combining qualitative and quantitative techniques. The design enabled direct researcher involvement in the stages of diagnosis, planning, implementation, and evaluation. Quantitative analysis was used to measure discharge process duration, while qualitative analysis identified waste using a Downtime Matrix, developed Current and Future State Maps through Value Stream Mapping, and supported the formulation of revised standard operating procedures. The study was conducted from July to October 2025 in the inpatient installation of the hospital. The sample consisted of 84 patients selected using purposive sampling. Lean implementation reduced discharge process Lead Time from 250.19 minutes to 129.50 minutes and increased the Value-Added Ratio (VAR) from 29.41% to 50.39%. In the inpatient insurance claim process, Lead Time decreased from 787.02 minutes to 549.55 minutes, while VAR improved from 10.47% to 49.76%. As conclusion, the findings demonstrate that Lean implementation is effective in reducing operational waste and improving efficiency in both patient discharge and inpatient insurance claim administration processes.Keywords: lean hospital; waiting time; patient discharge; health insurance claims; inpatient services